Applying Feminist Poststructuralism as a Framework for Exploring Infant Feeding Interactions in the Neonatal Intensive Care Unit - Jacqueline Elizabeth van Wijlen; Megan Aston (York University Libraries, 2019)
Childbearing/rearing families in Canada face a variety of conflicting discourses related to infant feeding, entrenched in a complex web of gendered, social, institutional and political discourses. For parents of preterm and/or critically ill infants, this area remains largely under-explored through a feminist lens. We offer a critical examination of the applicability of feminist poststructuralism (FPS) as a theory to explore infant feeding interactions in the neonatal intensive care unit (NICU). Scholarly literature from diverse perspectives, including nursing, healthcare, gender studies, and social sciences is critiqued and the use of FPS as a guiding framework for nursing research and praxis is discussed. We discuss FPS and the relevance of various discourses to explore the phenomenon of infant feeding interactions in the NICU. Ultimately, we propose that FPS does offer a relevant lens through which to critically examine infant feeding interactions and bring voice to the complex processes embedded in the NICU.